The sons of lucifer and the children of neptune: the anti-ottoman and anti-islamic polemical works of gerasimos vlachos - Olar, Ovidiu-Victor (Archaeus, 2016)
The aim of the present paper is to take a closer look at the anti-Ottoman and anti-Islamic stance of the 17th century Greek scholar Gerasimos Vlachos by analysing and placing in its context an encomium entitled Trionfo del Illustrissimo et Eccelentissimo Signor Alvise Mocenico Secondo Procurator di San Marco et Dignissimo Capitan General da Mar. Hastily recorded by Nestor Camariano and rarely mentioned in passing by the scholars dealing with Vlachos, this text is part of one of the Greek manuscripts of the Library of the Romanian Academy in Bucharest - BAR ms. gr. 889. Including (mainly) homilies preached in Candia between October 1649 and May 1650, the codex counts among the oldest autographs of "padre Don Girassimo Vlacho Greco di Creta predicatore". Delivered on November 25, 1649, after the sermon concluding the liturgy of the day, in the monastery of Saint Catherine in Candia, a dependency of the monastery with the same name from Mount Sinai, the encomium of Alvise Mocenigo celebrates the successful defence of the vital Martinengo cavalier of Candia during the first stages of the Cretan War (July - August 1649). Therefore, one is offered the possibility to look into the earliest depiction by Vlachos of the Ottoman Empire and of Islam, to see how (if ever) his opinion on the topic evolved over time.